2022
DOI: 10.1371/journal.pone.0278057
|View full text |Cite
|
Sign up to set email alerts
|

Post-acute sequelae of COVID-19 among hospitalized patients in Estonia: Nationwide matched cohort study

Abstract: Background Post-acute COVID-19 sequelae refers to a variety of health complications involving different organ systems that have been described among individuals after acute phase of illness. Data from unselected population groups with long-time follow up is needed to comprehensively describe the full spectrum of post-acute COVID-19 complications. Methods In this retrospective nationwide cohort study, we used data obtained from electronic health record database. Our primary cohort were adults hospitalized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…Among them, 225 studies were excluded for not meeting the inclusion criteria, leaving 5 investigations fulfilling the inclusion criteria (Fig. 1) [12][13][14][15][16].…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, 225 studies were excluded for not meeting the inclusion criteria, leaving 5 investigations fulfilling the inclusion criteria (Fig. 1) [12][13][14][15][16].…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
“…Similarly, few data were provided regarding the potential association between the severity of the index COVID-19 infection and the subsequent risk of new-onset HT. However, data from Al-Aly et al [ 14 ] and Tisler et al [ 16 ] suggested that this risk significantly increase in patients hospitalized and in those requiring intensive care treatments compared to those not hospitalized. Indeed, the hospitalization setting may indirectly reflect the severity of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding duplicates and preliminary screening, 1258 full-text articles were assessed for eligibility, 1250 studies were excluded for not meeting the inclusion criteria, leaving eight investigations fulfilling the inclusion criteria (Figure 1). [22][23][24][25][26][27][28][29]…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
“…Overall, 23,559,428 adult patients were included in this analysis. [22][23][24][25][26][27][28][29] Among them 1,595,984 had confirmed COVID-19 infection (Table 1). Although the demographic characteristics and the pre-existing comorbidities were not systematically recorded in all the investigations, the cohorts mainly consisted of middle-aged patients who were more frequently males (mean age 56, 1 year, 54.3% males).…”
Section: Characteristics Of the Population And Quality Assessmentmentioning
confidence: 99%